2019
DOI: 10.1016/j.jaci.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A combined immunodeficiency with severe infections, inflammation, and allergy caused by ARPC1B deficiency

Abstract: A combined immunodeficiency with severe infections, inflammation, and allergy caused by ARPC1B deficiency To the Editor:Recently, a novel syndrome of combined immunodeficiency, allergy, and ''auto''inflammation caused by mutations in the ARPC1B gene has been reported. [1][2][3][4] Analysis of patient-derived

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 7 publications
8
69
0
Order By: Relevance
“…Recent work has shown that the ARPC1 and ARPC5 isoforms differentially affect the actin nucleating properties of the Arp2/3 complex and the stability of the branched filament networks it generates (Abella et al, 2016). Furthermore, tissue-specific expression patterns of subunit isoforms, together with isoform-specific susceptibility to disease-causing point mutations, point to distinct physiological roles for particular Arp2/3 isoforms in nuclei positioning in skeletal muscle (Roman et al, 2017), as well as cytotoxic T lymphocyte maintenance and activity (Brigida et al, 2018;Kuijpers et al, 2017;Randzavola et al, 2019;Somech et al, 2017;Volpi et al, 2019;Roman et al, 2017;Kahr et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that the ARPC1 and ARPC5 isoforms differentially affect the actin nucleating properties of the Arp2/3 complex and the stability of the branched filament networks it generates (Abella et al, 2016). Furthermore, tissue-specific expression patterns of subunit isoforms, together with isoform-specific susceptibility to disease-causing point mutations, point to distinct physiological roles for particular Arp2/3 isoforms in nuclei positioning in skeletal muscle (Roman et al, 2017), as well as cytotoxic T lymphocyte maintenance and activity (Brigida et al, 2018;Kuijpers et al, 2017;Randzavola et al, 2019;Somech et al, 2017;Volpi et al, 2019;Roman et al, 2017;Kahr et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, among all the treatments options currently available for PID patients, hematopoietic stem cell transplantation (HSCT) is the most curative and reliable one. Multiple studies have reported significant efficacy of HSCT in different PID associated with synaptic defects ( 92 , 201 , 298 305 ). However, HSCT is a heavy surgical procedure that requires prior immunosuppressive conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations of ARPC1B give rise to multisystem inflammatory and immunodeficiency diseases (Brigida et al, 2018;Kahr et al, 2017;Kuijpers et al, 2017;Randzavola et al, 2019;Somech et al, 2017;Volpi et al, 2019), similar to Wiskott-Aldrich syndrome that is caused by mutations in the Arp2/3 activator WASP (Bosticardo et al, 2009). While some patients carry mutations causing premature protein termination and total loss of ARPC1B protein, four point mutations -W104S, A105V, V208F and A238T -have also been observed in patients (Brigida et al, 2018;Kahr et al, 2017;Volpi et al, 2019) (Figure 2A, right, purple spheres). W104, A105 and V208 are located in the core of the ARPC1B subunit β-propeller fold and this mutation likely destabilizes its tertiary fold, causing severely reduced protein levels in patients (Kahr et al, 2017).…”
Section: Isoform Specific Subunit Conformation and Determinants Of Acmentioning
confidence: 96%
“…Recent work has shown that the ARPC1 and ARPC5 isoforms differentially affect the actin nucleating properties of the Arp2/3 complex and the stability of the branched filament networks it generates (Abella et al, 2016). Furthermore, tissue-specific expression patterns of subunit isoforms, together with isoformspecific susceptibility to disease-causing point mutations, point to distinct physiological roles for particular Arp2/3 isoforms including cytotoxic T lymphocyte maintenance and activity (Brigida et al, 2018;Kahr et al, 2017;Kuijpers et al, 2017;Randzavola et al, 2019;Roman et al, 2017;Somech et al, 2017;Volpi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%